Simple-Made-Continuous Steel Bridges with Steel Diaphragms - Johnson, Robert I.; Atadero, Rebecca A. (Engineering Journal, 2017)
Simple-made-continuous (SMC) bridges are a relatively new innovation in steel bridge design. The majority of SMC bridges currently in use are constructed with concrete diaphragms. This article presents the results of numerical analysis and physical laboratory testing of an alternative simple-made-continuous (SMC) connection scheme that uses steel diaphragms in lieu of concrete diaphragms. A bridge using steel diaphragms was constructed by the Colorado Department of Transportation in 2005, and the connections on this bridge serve as the basis for the research discussed herein. The results of the analysis and testing provided information for the development of a design methodology based on the physical behavior of the SMC connection. The paper also compares the steel-diaphragm SMC connection to concretediaphragm SMC connections and demonstrates that the steel-diaphragm design has several desirable features. For a diaphragm cost, which is similar in cost to other SMC schemes, the steel-diaphragm design requires less total construction time. Additionally, because the girder ends are exposed, it is easy to verify that the girders have fully weathered (for weathering steel), they may be easily inspected, and there is no concern about cracking of a concrete diaphragm at re-entrant corners around the steel bridge girders.